ANALISIS DAMPAK KUALITAS PELAYANAN DAN KEPUASAN SEBAGAI MODERATING VARIABEL TERHADAP LOYALITAS NASABAH BANK BRI KANTOR KAS UNISMA - Mei Isnainiyah; N. Rachma; M. Hufron (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACT The intense competition in the banking world allows each bank to compete to attract as many customers as possible by building close relationships with its customers by providing a quality service that is good and different from other banks, to establish customer loyalty.The research aims to examine the effect of service quality on loyalty and the interaction between service qualty on loyalty moderated by costumer satisfaction. The population of this study was all costumers of BRI Bank UNISMA cash office. The sample used in this study is accidental sampling, namely, accidental sampling techniques with 96 respondents. The type of research is explanatory research. The data collection method used questionnaires so that anyone who come to the Bank would fill in the questionnaire that had been shared by the reshearchers.  The results of this study are that there’s a significant effect between service quality on costumer loyalty with the result of 0.001< 0.05, thus it can be said that the hypothesis is acceptable. And the second hypothesis has an interaction between service quality and loyalty with satisfaction as a moderator of variable with a significant value of 0.17<0.05.in this study using a test MRA ( Moderated Reression Analysis). Kywords : service quality, satisfaction, costumer loyalty.